Analysis of the impact of banking sector credits on the real sector in Nigeria - Sule Magaji; Ibrahim Musa; Saminu S. Dogo (International Journal of Management and Business Applied, 2023)
This study explains the effect of banking sector credit on Nigeria's real sector. It uses the Auto Regressive Distributed Lagged model. The bound testing result indicates that there is a long-run association among the variables of interest with Real GDP as the dependent variable. The result indicates that Commercial Bank Credit in the long and short run has a positive impact on Nigeria's GDP. Domestic private investment was found to have a negative relationship with the real sector in the long and short runs. The estimated long and short runs equation of the specified econometric model shows a significant positive relationship existing between government capital expenditure and real sector. In the short run, a significant increase in DPI, CBC, and GCE will bring a significant increase in RGDP. A unit increase in DPI, CBC, and GCE will bring about an increase in RGDP by 8.71 units, 3.18, and 0.42 respectively and the parameter estimate of DPI, CBC and GCE are statistically significant as computed by the t-value being -1.83, 2.19 and 1.95 respectively. The study reveals that utilization of bank credits to the real sector is significant toward achieving Nigerian economic growth. The study recommends improved banking sector credit.